A Novel Autoantibody against Plexin D1 in Patients with Neuropathic Pain. Issue 2 (3rd September 2018) - Fujii, Takayuki; Yamasaki, Ryo; Iinuma, Kyoko; Tsuchimoto, Daisuke; Hayashi, Yoshinori; Saitoh, Ban‐yu; Matsushita, Takuya; Kido, Mizuho A.; Aishima, Shinichi; Nakanishi, Hiroshi; Nakabeppu, Yusaku; Kira, Jun‐ichi
Abstract : Objective: To identify novel autoantibodies for neuropathic pain (NeP). Methods: We screened autoantibodies that selectively bind to mouse unmyelinated C‐fiber type dorsal root ganglion (DRG) neurons using tissue‐based indirect immunofluorescence assays (IFA) with sera from 110 NeP patients with various inflammatory and allergic neurologic diseases or other neuropathies, and 50 controls without NeP including 20 healthy subjects and 30 patients with neurodegenerative diseases or systemic inflammatory diseases. IgG purified from IFA‐positive patients' sera was subjected to Western blotting (WB) and immunoprecipitation (IP) using mouse DRG lysates. Immunoprecipitates were analyzed by liquid chromatography tandem mass spectrometry (LC‐MS/MS) to identify target autoantigens. Results: Antiunmyelinated C‐fiber type DRG neuron antibodies were more frequent in patients with NeP than non‐NeP subjects (10% vs 0%; p < 0.05). These autoantibodies were all from the IgG2 subclass and colocalized mostly with isolectin B4‐ and P2X3‐positive pain‐conducting small neurons but not with S100β‐positive myelinated neurons. WB revealed a common immunoreactive band (approximately 220kDa). IP and LC‐MS/MS studies identified plexin D1 as a target autoantigen. Immunoadsorption tests with recombinant human plexin D1 in IFA revealed that all 11 anti–small DRG neuron antibody‐positive patients had anti–plexin D1 antibodies. Application of anti–plexin D1 antibody‐positive patient sera to cultured DRG neurons increased membrane permeability, leading to cellular swelling. NeP patients with anti–plexin D1 antibodies commonly developed burning pain and current perception threshold abnormalities for C‐fibers. Main comorbidities were atopy and collagen‐vascular disease. Immunotherapies ameliorated NeP in 7 treated cases. Interpretation: Anti–plexin D1 antibodies are a novel biomarker for immunotherapy‐responsive NeP. Ann Neurol 2018;84:208–224